Comparison of the Copenhagen Index versus ROMA for the preoperative assessment of women with ovarian tumors. Issue 2 (22nd November 2017) - Minar, Lubos; Felsinger, Michal; Cermakova, Zdenka; Zlamal, Filip; Bienertova‐Vasku, Julie
Abstract: Objective: To compare the Copenhagen Index (CPH‐I) and the Risk of Ovarian Malignancy Algorithm (ROMA) in the differential diagnosis of ovarian tumors. Methods: In a retrospective study, data were reviewed from women with ovarian tumors who attended University Hospital Brno, Czech Republic, between July 2011 and June 2015. The women were classified into the benign tumor group or malignant tumor group (borderline and malignant tumors). Serum levels of CA125 and HE4 were extracted from medical records. The two tumor indices were calculated using relevant clinical data. Results: Among 267 included women, 110 had benign tumors, 42 had borderline ovarian tumors, and 115 had malignant tumors. The two indices showed similar discriminatory performance with no significant differences ( P >0.05). In the differentiation of benign tumors from all stages of borderline tumor and ovarian cancer, ROMA showed a sensitivity of 71% at a specificity of 88%, whereas CPH‐I showed a sensitivity of 69% at a specificity of 85%. Conclusion: CPH‐I is a potential tumor index that is independent of menopausal status. It might be applied as a simple alternative to ROMA in settings of basic medical care. Abstract : The Copenhagen Index is a simple tumor index applicable to the preoperative assessment of women with ovarian tumor in settings of basic medical care.